Identifikasi Faktor-Faktor Kejadian Anemia Pada Ibu Hamil Trimester II Di Puskesmas Wilayah Kerja Kabupaten Semarang - Syifa Fauziah; Rifatolistia Tampubolon; Fiane De Fretes (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: to identify  the factors of anemia in pregnant women at the Semarang District Health Center.Methods: This article Descriptive quantitative research method with cross sectional research design. The population in this study were 40 trimester II pregnant women in the working area of Semarang Regency. The sampling technique used purposive sampling. Data collection using a questionnaire, was conducted in February - March 2020. The results of data collection are presented in table form and described.Results:  The results show that 85% of pregnant women are not the age group at risk for pregnancy. The latest education for pregnant women is 60%, namely SMA. The occupation of pregnant women is 42.5% as an employee. The economic income of a pregnant woman's family is 40% below the UMR Semarang Regency. The level of knowledge of pregnant women about pregnancy anemia is 60% in the sufficient category. In consuming Fe tablets, pregnant women are categorized as less obedient. Diet of pregnant women who consume less iron-containing foods and often consume tea.Conclusion:  The conclusion of this study is that the factors of work, factors of family economic status, factors of knowledge level, factors of compliance with Fe tablets and dietary factors affect the incidence of anemia in pregnant women.